PENGARUH PENGGUNAAN MEDIA VIDEO PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN 292/VI SUNGAI LALANG TAHUN PELAJARAN 2025/2026 - Diva Apri Mulya; Ovi Cania; sevira Melati; Sindi Wulandini; Barokah Tri Wijayanti; M.Ali Basroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aimed to determine the effect of using instructional video media on students' learning interest in mathematics among fourth-grade students at SDN 292/VI Sungai Lalang in the 2025/2026 academic year. The study was motivated by the low level of students' learning interest in mathematics, as indicated by their lack of enthusiasm and participation during learning activities that were still dominated by textbooks, worksheets, and lecture methods. This research employed a quantitative approach using a descriptive quantitative method. The population consisted of all 22 fourth-grade students of SDN 292/VI Sungai Lalang selected through total sampling. Data were collected using Likert-scale questionnaires to measure the use of instructional video media and students' learning interest. The data were analyzed using a 3×3 contingency table and the Chi-Square (χ²) test. The results showed that the calculated χ² value of 22.34 was higher than the χ² table value of 9.488 at the 5% significance level; therefore, the alternative hypothesis was accepted. The contingency coefficient value of 0.71 indicated a strong relationship between the use of instructional video media and students' learning interest. It can be concluded that the use of instructional video media has a significant effect and a strong relationship with students' learning interest in mathematics among fourth-grade students at SDN 292/VI Sungai Lalang in the 2025/2026 academic year. Keywords: instructional video media, learning interest, mathematics, elementary school.